Elucidation of the Bovine Intramammary Bacteriome and Resistome from healthy cows of Swiss dairy farms in the Canton Tessin - Romanò, Alicia; Ivanovic, Ivana; Segessemann, Tina; Vazquez Rojo, Laura; Widmer, Jérôme; Egger, Lotti; Dreier, Matthias; Sesso, Lorenzo; Vaccani, Michael; Schuler, Martin; Frei, Daniel; Frey, Juerg; et al. (Frontiers in Microbiology, 2023)
Healthy, untreated cows of nine dairy herds from the Swiss Canton Tessin were analyzed three times within one year to identify the most abundant species of the intramammary bacteriome. Aseptically collected milk samples were cultured and bacteria identified using MALDI-TOF. Of 256 cows analyzed, 96% were bacteriologically positive and 80% of the 1024 quarters were positive for at least one bacterial species. 84.5% of the quarters were healthy with somatic cell counts (SCC) < 200'000 cells/ml, whereas 15.5% of the quarters showed a subclinical mastitis (SCC ≥ 200'000 cells/ml). We could assign 1288 isolates to 104 different bacterial species including 23 predominant species. Nonaureus staphylococci and mammaliicocci (NASM) were most prevalent (14 different species; 73.5% quarters). Staphylococcus xylosus and Mammaliicoccus sciuri accounted for 74.7% of all NASM isolates. To describe the intramammary resistome, 350 isolates of the predominant species were selected and subjected to short-read whole genome sequencing (WGS) and phenotypic antibiotic resistance profiling. While complete genomes of eight type strains were available, the remaining 15 were de novo assembled with long reads as a resource for the community. The 23 complete genomes served for reference-based assembly of the Illumina WGS data. Both chromosomes and mobile genetic elements were examined for antibiotic resistance genes (ARGs) using in-house and online software tools. ARGs were then correlated with phenotypic antibiotic resistance data from minimum inhibitory concentration (MIC). Phenotypic and genomic antimicrobial resistance was isolatespecific. Resistance to clindamycin and oxacillin was most frequently observed (65% and 30%) in Staphylococcus xylosus but could not be linked to chromosomal or plasmid-borne ARGs. However, in several cases, the observed antimicrobial resistance could be explained by the presence of mobile genetic elements like tetK carried on small plasmids. This represents a possible mechanism of transfer between non-pathogenic bacteria and pathogens of the mammary gland within and between herds. The -to our knowledge-most extensive bacteriome reported and the first attempt to link it with the resistome promise to profoundly affect veterinary bacteriology in the future and are highly relevant in a One Health context, in particular for mastitis, the treatment of which still heavily relies on antibiotics.